The Significance of Trimester-Specific Thyroid Hormones Reference Intervals in Iraqi Pregnant Women - Ahmad, Hani Moslem; Alabdaly, Moayad Aziz; Sulaiman, Khairaldeen Mohammed (UI Scholars Hub, 2022)
In Iraq, there is no obvious considerable data regarding trimester-specific reference intervals of thyroid hormones despite documented multiple physiological hormonal changes during pregnancy. Thus, this study aimed to determine trimester-specific reference intervals for serum TSH, FT3, and FT4 and assess the incidence of thyroid function test misinterpretation and misdiagnosis among pregnant women using non-pregnant reference intervals. A thyroid function test was performed for 774 enrolled pregnant women. Reference intervals of TSH, FT3, and FT4 were ascertained in each pregnancy trimester. It was then compared to the adult non-pregnant values, and the incidence of misinterpretation was later calculated. TSH and FT4 reference interval values were lower than non-pregnant reference interval values. The application of non-pregnant women references values in pregnant women caused a serious misinterpretation and misdiagnosis in 66 (8.5%) pregnant women regarding TSH, and 34 (4.4%) pregnant women regarding FT4, while no misdiagnosis was noticed regarding FT3. The trimester-specific reference interval values of TSH, FT3, and FT4 in Iraqi pregnant women showed an obvious variation from non-pregnant reference intervals and the urgent advice to use the trimester-specific reference intervals to avoid misclassification of thyroid dysfunction during pregnancy.